Desain Situs Web Responsif untuk Profil dan Layanan Kesehatan Pusat Kesehatan Masyarakat Ngasem dengan Fitur Asisten Informasi - Ahmad wildan muzaki; Sucipto Sucipto; Muhammad Najibulloh Muzaki (JESII: Journal of Elektronik Sistem InformasI, 2026)
The advancement of information technology has encouraged healthcare institutions to improve the accessibility and quality of information services provided to the public. UPTD Puskesmas Ngasem still relied on conventional media and social platforms for disseminating information, making it difficult for the community to obtain accurate and up-to-date health service information in a centralized manner. This study aims to design and develop a responsive web-based health information system equipped with an information assistant feature to facilitate public access to health service information. The system was developed using the Waterfall method, which consists of requirements analysis, system design, implementation, testing, and maintenance stages. Laravel was utilized as the web development framework, MySQL as the database management system, and n8n workflow automation integrated through Laravel webhooks to support the information assistant feature. The system provides information related to health services, doctor schedules, health articles, service tariffs, health activities, and public feedback. System testing was conducted using the Black Box Testing method to evaluate functional suitability. The results indicate that all system functionalities operate according to user requirements and can be accessed effectively across desktop, tablet, and smartphone devices. The implementation of the information assistant feature also improves the efficiency of information delivery and helps reduce repetitive inquiries received by healthcare staff. Therefore, the developed system can support more effective, accessible, and responsive health information services for the community.